Challenges of Local Public Administration in Conflict -Affected Countries: Case of Hadhramaut Governorate in Yemen - Ba Abbad, Istanbool (AUC Knowledge Fountain, 2024)
This thesis explores the challenges local public administration faced in Hadhramaut, Yemen, and explores avenues for reform. The study's main question is: "What are the main challenges confronting local public administration in Hadhramaut, and what pathways can be pursued for reform?" Hadhramaut, known for its relative stability within Yemen's political unrest, was selected as the case study. Despite its stability, the governorate struggles with challenges arising from the conflict. The research aimed to uncover these challenges and suggest guidelines for recovery, envisioning the governorate as a model for the country. The research aimed to investigate the challenges confronted by public sector employees who are responsible for executing daily tasks and service delivery. The methodology adopted a case study approach, focusing on the Hadhramaut governorate and utilizing qualitative methods, particularly one-on-one semi-structured interviews with thirteen participants representing diverse managerial levels within government offices. The findings illuminated institutional and managerial challenges. Institutional challenges derive from organizational structures and external interactions, while managerial directly impact decision-making and operational processes. The study recognized issues such as the absence of monitoring and evaluation mechanisms, lack of accountability principles, and other political and financial difficulties. Addressing these challenges in Hadhramaut needs a context-specific, comprehensive reform strategy. The study proposes tailored recommendations drawing on global reform experiences and suit the Yemeni context, aiming to bolster the local public administration system in Hadhramaut.